Revision of Trachelissa Aurivillius, 1912 (Insecta: Coleoptera: Cerambycidae) - Quintino, Hingrid Yara S.; Monné, Marcela L. (Zootaxa, 2014)
A revision of the genus Trachelissa Aurivillius, 1912, based on a study of external morphology and terminalia, is presented. The genus and its species are redescribed. Five species are recognized, two of which are described as new: T. bella sp. nov. from Bolivia and T. opaca sp. nov. from Argentina. A new host plant for T. maculicollis Audinet-Serville, 1834 is recorded. A key to all species, and their photographs and distribution maps are provided.